An Iconographic Reading of the Ḥajj Through the Certificate ORB.50/11 and Other Printed Copies from the 19th Century - Carro Martín, Sergio (Eikón / Imago, 2023)
From its beginnings, the Islamic pilgrimage (ḥajj) raised a problem for those Muslims who could not travel to Mecca. As a religious precept and, therefore, mandatory, the Islamic jurisprudence looked for a legal alternative to make the pilgrimage by proxy. Consequently, at the end of the 11th century the pilgrimage certificates, legal documents that accredited the fulfillment of this precept through a delegate, came to light. The uneven course of these documents in the material culture of the Islamic pilgrimage makes especially interesting the analysis of those produced from the 19th century, when they seem to resurface in modern collections. This article presents one of those certificates, preserved in the British Library (ORB.50/11). It contains several illustrations of the main holy places of Islam and a design similar to other copies scattered in European collections. The comparative study of its iconography will allow us to analyze the standardization process of these certificates and their copies before the scroll format was completely discarded.